Influence of a high pulsed magnetic field on the tensile properties and phase transition of 7055 aluminum alloy. (28th October 2016) - Li, Gui-Rong; Cheng, Jiang-Feng; Wang, Hong-Ming; Li, Pei-Si; Li, Chao-Qun
Abstract: The effect of a high pulsed magnetic field on the tensile properties and microstructure of 7055 alloy were investigated. In the tensile properties test, the pulsed magnetic field was applied to improve the tensile strength and elongation via the magnetoplasticity effect. The results show that when the magnetic induction intensity ( B ) is 3 T, the tensile strength and elongation arrives at the maximum synchronously, which has been enhanced by 7.9% and 20% compared to the relevant 576.5 MPa ( σ b ), 7.5% ( δ ) of the initial sample without magnetic field treatment. The high magnetic field takes effect by altering the spin state of free electrons stimulated between the dislocations and obstacles; afterwards, the structural state of the radical pair is converted from the singlet state with high bonding energy to the triplet state with low bonding energy. Under this condition, the dislocation mobility is enhanced and it becomes easier for a dislocation to surmount the obstacles. The residual stress in the sample is connected closely with the long distance stress generated from the dislocation behavior. At 3 T, the residual stress arrived at the minimum of 16 MPa. Moreover, in the presence of a magnetic field, the common η (MgZn2 ) in the grain boundary dissolved and moved to internal grains because of the concentration difference, which helped to enhance the tensile strength and toughness of the materials. Finally, the fracture morphology was analyzed by scanning electronic microscopy. The fracture characteristic matches with the plasticity property.